Intimacies, Critical Consumption and Diverse Economies
XII, 235 p. 6 illus.
Keywords: This collection explores the relationships between the emotional and material, engaging with and developing the debates surrounding the emotional and material labour involved in producing and reproducing domestic and intimate spaces. The contributions examine the geographies and spaces of consumption in international and local-global spheres.